2007
DOI: 10.1016/j.cub.2007.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Capicua Regulates Cell Proliferation Downstream of the Receptor Tyrosine Kinase/Ras Signaling Pathway

Abstract: Signaling via the receptor tyrosine kinase (RTK)/Ras pathway promotes tissue growth during organismal development and is increased in many cancers [1]. It is still not understood precisely how this pathway promotes cell growth (mass accumulation). In addition, the RTK/Ras pathway also functions in cell survival, cell-fate specification, terminal differentiation, and progression through mitosis [2-7]. An important question is how the same canonical pathway can elicit strikingly different responses in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 26 publications
3
111
0
1
Order By: Relevance
“…18 It was previously demonstrated that substitution mutation R505W (corresponding to R215W in human CIC) at the HMG box led to impaired eye development in Drosophila. 19 Moreover, the indels were predominantly of frameshift and small inframe deletions at functional domains including the HMG box and the CI motif that are predicted to disrupt CIC function. The mutation profile suggests that CIC function is likely compromised in oligodendroglial tumors harboring CIC mutations.…”
Section: Cic Mutationsmentioning
confidence: 99%
“…18 It was previously demonstrated that substitution mutation R505W (corresponding to R215W in human CIC) at the HMG box led to impaired eye development in Drosophila. 19 Moreover, the indels were predominantly of frameshift and small inframe deletions at functional domains including the HMG box and the CI motif that are predicted to disrupt CIC function. The mutation profile suggests that CIC function is likely compromised in oligodendroglial tumors harboring CIC mutations.…”
Section: Cic Mutationsmentioning
confidence: 99%
“…In Drosophila, Cic controls anteroposterior and dorsoventral embryonic polarity, the subdivision of the lateral ectoderm, and pattern formation in several tissues (1,(3)(4)(5)(6). In addition, Cic negatively regulates the growth of imaginal discs and the midgut (7,8). In humans, a single Cic ortholog (CIC) has been implicated in the neurodegenerative disease spinocerebellar ataxia 1 (SCA1) (9), and recently mutations in CIC have been found in the majority of oligodendroglioma cases, suggesting that CIC is a tumor suppressor (10)(11)(12).…”
mentioning
confidence: 99%
“…In both Drosophila and mammals, Cic functions as a primary sensor of signaling downstream of the receptor tyrosine kinase (RTK)/extracellular signal-regulated kinase (ERK) pathway (2,(5)(6)(7)(8)(13)(14)(15)(16). According to the current model, activation of RTK signaling results in the accumulation of doubly phosphorylated activated ERK, which directly binds to and phosphorylates Cic (5).…”
mentioning
confidence: 99%
“…Ils ont constaté qu'en absence de PTP10D, l'expression du facteur de transcription Capicua diminue, ce qui reflète l'activation de la voie EGF [5]. De plus, l'utilisation de deux ARNi différents ciblant, d'une part, PTP10D et, d'autre part, le récepteur à l'EGF (EGFR) rétablit la compétition cellulaire.…”
Section: Quelles Voies Sont Mises En Jeu ?unclassified